1985
DOI: 10.1002/jcp.1041230113
|View full text |Cite
|
Sign up to set email alerts
|

Utilization and formation of amino acids by chicken epiphyseal chondrocytes: Comparative studies with cultured cells and native cartilage tissue

Abstract: Utilization and production of amino acids by primary cultures of chicken growth plate epiphyseal chondrocytes grown in Dulbecco's modified Eagle's medium supplemented with 10% fetal bovine serum were investigated in both short-term (6-72 h) and long-term (3-24 day) cultures. Comparative studies were made on levels of free amino acids in chicken blood plasma and serum, and in extracellular fluids from different regions of growth plate cartilage and from two types of muscle. Chondrocytes rapidly consumed glutami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…For serum containing DATP5 medium, cells were supplied with Dulbecco's modified Eagle's medium (DMEM) supplemented with 5% fetal bovine serum (FBS), 8 amino acids found to be enriched in the extracellular fluid of the avian growth plate [Ishikawa et al, 1985], insulin-transferrin-selenite (ITS), and 1 mM Na 2 HPO 4 from day 6 or 7 onward. For serum-free HL-1 medium, on day 6 or 7, cells were supplied with a medium composed of a 1:1 mixture of DMEM (containing 10% FBS) and serum-free HL-1 medium, and from day 10 onward, the cells were given only HL-1.…”
Section: Materials and Methods Chondrocyte Culturesmentioning
confidence: 99%
“…For serum containing DATP5 medium, cells were supplied with Dulbecco's modified Eagle's medium (DMEM) supplemented with 5% fetal bovine serum (FBS), 8 amino acids found to be enriched in the extracellular fluid of the avian growth plate [Ishikawa et al, 1985], insulin-transferrin-selenite (ITS), and 1 mM Na 2 HPO 4 from day 6 or 7 onward. For serum-free HL-1 medium, on day 6 or 7, cells were supplied with a medium composed of a 1:1 mixture of DMEM (containing 10% FBS) and serum-free HL-1 medium, and from day 10 onward, the cells were given only HL-1.…”
Section: Materials and Methods Chondrocyte Culturesmentioning
confidence: 99%
“…For example, Ishikawa et al [69] reported that the overall concentrations of AAs in chicken cartilage (18.3 -55.3 mM) and muscle (44.3 -114.7 mM) were generally higher than in serum (21.4 mM) and blood plasma (6.3 mM). More specifically, they showed that the concentrations of charged AAs, such as Arg, Asp and Glu, which are strongly involved in mineralization, were 0.44, 3.76 and 15.37 mM in chicken hypertophic cartilage extracellular fluid (ECF), whereas it was 0.37, 0.06 and 0.16 mM, respectively, in blood plasma [69]. They also revealed that increasing the concentration of eight AAs (Asp, Glu, Ser, Gly, Ala, Pro, taurine (Tau), and asparagine (Asn)) in the culture medium to the level present in the native cartilage ECF remarkably stimulated the formation of alkaline phosphatase (AP) and AP-rich matrix vesicles (MV) by chondrocytes [70].…”
Section: Effect Of Amino Acids On Mineralization In Vivomentioning
confidence: 99%
“…HL-1 chemically defined proprietary media contains transferrin, testosterone, sodium selenite, ethanolamine, saturated and unsaturated fatty acids, and stabilizing proteins (less than 30 mg/ml) and is supplemented with 10 mM b-glycerophosphate. DATP5 medium was prepared from DMEM basal medium by addition of eight amino acids [Ishikawa et al, 1985], insulin (5 mg/ml)-transferrin (5 mg/ml)-selenite (5 ng/ml), and 5% defined FBS; it had a total Pi level of 1.9 mM (0.9 mM from DMEM þ 1 mM added Na 2 HPO 4 ) and Ca 2þ of 1.8 mM [Ishikawa and Wuthier, 1992]. All culture media contained 100 IU/ml of penicillin, 100 mg/ml streptomycin, and 0.25 mg/ml amphotericin B.…”
Section: Cell Culturementioning
confidence: 99%
“…Based on the authors' previous analyses of electrolytes [Wuthier, 1969[Wuthier, , 1971[Wuthier, , 1977, amino acids [Ishikawa et al, 1985] and other constituents, a culture media was constructed that closely matches GP extracellular fluid. This culture medium, DATP5, fully supports proliferation, differentiation, and mineralization of primary cultures of GP chondrocytes isolated from rapidly growing broiler-strain chickens [Ishikawa et al, 1986;Wu et al, 1989Wu et al, , 1995Ishikawa and Wuthier, 1992].…”
mentioning
confidence: 99%